Pengaruh Model Pembelajaran Picture and Picture terhadap Penguasaan Kosakata Bahasa Arab Siswa Sekolah Dasar (MI/SD) di Tasikmalaya - Khudoriyah, Ana Maryam Fadlah; Maksum, Khanif (Indonesian Journal of Elementary Education and Teaching Innovation, 2025)
This study aims to examine the effect of the picture and picture learning model on the mastery of Arabic vocabulary in first-grade students of MI Miftahul Huda As-Saodah. Specifically, this study identifies whether there is an effect of implementing this model, and analyzes the level of Arabic vocabulary mastery of students after the application of the picture and picture model on the material أسماء الفواكه.The research method used is quasi-experimental with a non-equivalent control group design. The research subjects involved all 36 first-grade students, who were then divided into two groups through random sampling technique. Class 1A was selected as the experimental class and class 1B as the control class. The location of this research is MI Miftahul Huda As-Saodah. The data analysis techniques used include normality test, homogeneity test, and independent sample t-test.The results showed that: the implementation of the picture and picture learning model had been carried out in accordance with the lesson plan implementation, as indicated by the higher average value of the experimental class compared to the control class. There is a significant effect of the application of the picture and picture learning model on the mastery of Arabic vocabulary of first-grade students of MI Miftahul Huda As-Saodah in the 2022/2023 academic year. This is evidenced by the t-test results which show a significance value of 0.000. Therefore, it can be concluded that the picture and picture learning model is effective in improving the mastery of Arabic vocabulary in students.Keyword : Picture and Picture Learning Model, Arabic Vocabulary